Implementasi Enkripsi dan Dekripsi dengan Metode RC4 untuk Pengamanan Data Sistem Informasi - Saragih, Uli Sholihah; Sakethi, Dwi (Universitas Lampung, 2017)
In 2015, Lecturer Activity Information System (SIKSEN) Department of Computer Science Unila experiencing data attacks (hack) which resulted in data lecturer activities can not appear in the information system. Attacking the data that occurred is one result of the lack of data security in Information Systems Computer Science Department. One way to secure data is to use cryptographic techniques. Cryptography is the way it does by encoding the original message into an elusive random message. In cryptography there are two main processes namely encryption and decryption. Encryption represents converting the original message into a password message, while decryption is the process of returning the password message to the original message. The method used is Rivest Code 4 (RC4) because this method is one of the methods that the encoding result (ciphertext) has the same character length as the original message (plaintext). This method consists of three main stages: KSA (Key Scheduling Algorithm), PRGA (Pseudo Random Generation Algorithm) and XOR process. The data used in this study is the data of Unila Computer Science students, amounting to 970 student data consisting of 25 columns of data. Testing is done by testing whether the number of original message characters is the same as the password and how much data is successfully encrypted and decrypted. The test results obtained that 970 data successfully encrypted and 970 data successfully decrypted with the same number of characters between the original message and password.